The effect of acetylene treatment on some physical and chemical properties of mangoes (Mangifera Indica Linn. Var. Carabao) - Castro, Ana Corina M.; Gatchalian, Miflora M. (1968., 1968)
The study was conducted with the object of determining the effect of acetylene-treatment on some of the physical and chemical properties of mangoes (Mangifera indica Linn. var. carabao) with special reference to flavor. Calcium carbide was used to generate acetylene. Mangoes were exposed to 3 levels of calcium carbide: 5, 10 and 15 grams. The differences among the treated samples were not as marked as those between the treated and the untreated. Acetylene-treatment effected an increase in respiration, a faster yellowing of peel and pulp, a more rapid decrease in acidity and a more rapid increase in pH, soluble solids and total sugars. Final concentrations of acids and sugars, however, were the same for both the treated and untreated samples. Ascorbic acid was not affected at all. The treated samples were as acceptable but were more susceptible to decay than the untreated ones.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mango -- Philippines